Blind-prediction: Estimating the consequences of vented hydrogen deflagrations for homogeneous mixtures in 20-foot ISO containers. (2nd April 2019) - Skjold, T.; Hisken, H.; Lakshmipathy, S.; Atanga, G.; Carcassi, M.; Schiavetti, M.; Stewart, J.R.; Newton, A.; Hoyes, J.R.; Tolias, I.C.; Venetsanos, A.G.; Hansen, O.R.; et al.
Abstract: This paper summarises the results from a blind-prediction study for consequence models used for estimating the reduced explosion pressure and structural response in vented hydrogen deflagrations. The work is part of the project Improving hydrogen safety for energy applications through pre-normative research on vented deflagrations (HySEA). The scenarios selected for the blind-prediction entailed vented explosions with homogeneous hydrogen-air mixtures in a 20-foot ISO (International Organization for Standardization) container. The test program included two configurations and six experiments, i.e. three repeated tests for each scenario. The comparison between experimental results and model predictions reveals reasonable agreement for some of the models, and significant discrepancies for others. The results from the first blind-prediction study in the HySEA project should motivate developers to improve and validate their models, as well as to update documentation and guidelines for users of the models. Highlights: Summary of results from the first blind-prediction benchmark exercise in the HySEA project. Full-scale vented hydrogen deflagration experiments in 20-foot ISO containers. Reasonable agreement between model predictions and experiments for most models. Significant spread in predictions from different users of the same model system. Significant effect of grid resolution for some model systems.